Pok Pek Prak: Sundanese Local Wisdom as the Foundation for Financial Reporting among Micro, Small, and Medium Enterprises (MSMEs) - Yanti, Yanti; Sujaya, Fista Apriani; Sihabudin, Sihabudin; Savitri, Citra (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study was conducted to examine the extent to which the Pok Pek Prak culture is used as a conceptual foundation in the preparation of financial statements. Design/methodology/approach – This research employs a qualitative method with a phenomenological approach. The data used consists of primary data obtained through interviews with MSMEs (Micro, Small, and Medium Enterprises) managers operating in the culinary sector. Findings – The results show that the Pok Pek Prak culture has already been implemented in the management of MSMEs. Furthermore, this culture should be applied as a foundation in financial reporting, as it reflects the values of Sundanese local wisdom. The values embodied in Pok Pek Prak can be instilled in individuals managing financial reports, thereby enhancing the quality and accountability of those reports. Originality – This study explores the extent to which the Pok Pek Prak culture can serve as a conceptual foundation for the preparation of MSME financial statements in West Java. Keywords: Pok Pek Prak, Sundanese local wisdom, MSMEs. Paper Type Research Result